2006
DOI: 10.3892/ijo.29.3.665
|View full text |Cite
|
Sign up to set email alerts
|

Oncostatic effects of the indole melatonin and expression of its cytosolic and nuclear receptors in cultured human melanoma cell lines

Abstract: Abstract.Melatonin has been shown to have oncostatic effects on malignant melanoma in vitro and in vivo. We studied the growth suppressive effects of melatonin over a wide range of concentrations in four melanoma cell lines (SBCE2, WM-98, WM-164 and SKMEL-188) representative for different growth stages and phenotype. Melanoma cells were incubated with melatonin 10 -12 -10 -3 M, and proliferation and clonogenicity was assessed at 12 h and 14 days, respectively. We also determined the expression of cytosolic qui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
88
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(101 citation statements)
references
References 68 publications
9
88
0
4
Order By: Relevance
“…The assay followed standard methodology used in our laboratory as described previously (18,29,76 control) were added with media being changed every 3 days. After 7 days of incubation, the colonies were fixed and then stained with 2% crystal violet, and the number and size of the colonies were measured using an ARTEK counter 880 (Dynex Technologies, Chantilly, VA).…”
Section: Colony-forming Assaymentioning
confidence: 99%
“…The assay followed standard methodology used in our laboratory as described previously (18,29,76 control) were added with media being changed every 3 days. After 7 days of incubation, the colonies were fixed and then stained with 2% crystal violet, and the number and size of the colonies were measured using an ARTEK counter 880 (Dynex Technologies, Chantilly, VA).…”
Section: Colony-forming Assaymentioning
confidence: 99%
“…In addition, several clinical studies have reported positive results with melatonin in patients with metastatic malignant melanoma. Most recently, melatonin has been shown to have tumorostatic effect in human melanoma cell lines of different behavior [65]. The intensity of the oncostatic response to melatonin was related to the cell-line -specific pattern of melatonin cell surface and nuclear receptor expressions [65].…”
Section: Melatonin Receptorsmentioning
confidence: 99%
“…Most recently, melatonin has been shown to have tumorostatic effect in human melanoma cell lines of different behavior [65]. The intensity of the oncostatic response to melatonin was related to the cell-line -specific pattern of melatonin cell surface and nuclear receptor expressions [65]. Thus, targeting melatonin receptors may represent a realistic approach in melanoma therapy [42].…”
Section: Melatonin Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, melatonin in pharmacological concentrations suppresses proliferation of the melanoma cells [18].…”
Section: Discussionmentioning
confidence: 99%